Effectiveness of an online multimodal rehabilitation program in long COVID patients: a randomized clinical trial - Sandra León-Herrera; Bárbara Oliván-Blázquez; Raquel Sánchez-Recio; Fátima Méndez-López; Rosa Magallón-Botaya; Rafael Sánchez-Arizcuren (BMC, 2024)
Abstract Background Digital interventions are expected to facilitate the treatment of patients suffering from Long COVID. This trial assesses the effectiveness of a multimodal rehabilitation program -comprising both online and synchronous components- in managing the characteristic symptoms of Long COVID and, consequently, in improving quality of life. It also aims to identify which changes in measured variables from baseline (T0) to post-intervention (T1) predict an improvement in quality of life. Methods A blind randomized controlled trial was conducted with two parallel groups: (1) the control group, which received usual treatment from the primary care physician and (2) the intervention group, which received usual treatment in addition to an online multimodal rehabilitation program. The data were collected at two time points: prior to the start of the intervention and three months after it. The main outcome variable was quality of life, encompassing both mental health and physical health-related quality of life. Sociodemographic and clinical variables were collected as secondary variables. Results A total of 134 participants (age 48.97 ± 7.64; 84.33% female) were included and randomized into the control group (67 participants) and the intervention group (67 participants). Comparative analyses conducted before and after the intervention showed a significant improvement in the mental health-related quality of life of the participants who received the intervention, with a mean increase of 1.98 points (p < 0.05). Linear regression analyses revealed that both received the intervention (b = 3.193; p < 0.05) and an increased self-efficacy (b = 0.298; p < 0.05) were predictors of greater improvement in mental health-related quality of life.